Talent Management in increasing Company Competitiveness in the Business world - Adi Rahmat; Yulihardi Yulihardi; Afrida Afrida (Universitas Dharma Wacana, 2022)
Management with human talent skills should be understood regarding employee performance in private or public entity businesses and staff performance enhancement and contributing to ethical and socially responsible activities. Management with human talent abilities has gained significant importance today; hence, each firm must have adequate knowledge of this functional area. This research focuses on the factors that influence human talent skills in organizations since its theoretical development, where concepts and theories of human talent and skills management are discussed. Additionally, the discussion presents the findings of empirical studies conducted on human talent development in various companies worldwide. In contrast to what is conceptually described, Indonesia.